Epigenetics applied to epidemiology: investigating environmental factors and lifestyle influence on human health - Motta, Valeria; Bonzini, Matteo; Grevendonk, Lotte; Iodice, Simona; Bollati, Valentina (La Medicina del Lavoro, 2017)
Epigenetics modifications, that include variations in DNA methylation, histone acetylation and micro RNA (miRNA) expression, co-operate together, influencing genome expression and function, in response to exogenous stimuli or exposures. Thus, epigenetic tools applied to epidemiology are useful in investigating, at the population level, the relationships between exposures to environmental, lifestyle, genetic, socioeconomic risk factors, and the epigenome, and/or specific health outcomes. But the choice of an appropriate study design and of valid epidemiological methods has a key role in determining the achievement of the study. This review summarises available evidence about the role of the most investigated epigenetic mechanisms in mediating lifestyle or environmental exposure effects on human health, considering the entire life-course, from in-utero to adulthood. Moreover, we illustrate the most important variables that should be properly considered when designing an epigenetic epidemiology study: the choice of an appropriate study design, a proper estimation of the required sample size, a correct biological sample selection, a validation strategy for epigenetics data, and an integrated exposure assessment methodology.